2014
DOI: 10.1089/zeb.2014.0977
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Number of Subjects on the Dark/Light Preference of Zebrafish (Danio rerio)

Abstract: This research aims to describe the effects of a variable number of Danio rerio fish subjects, ranging from one to eight, in the light/dark box preference test. Four hundred eighty adult male short-finned phenotype zebrafish were tested in the light/dark box. There were four groups in this experiment and a different number of subjects was used in each group: the control group had only one subject, whereas the experimental groups had either two, four, or eight subjects simultaneously inside the apparatus in ever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…The testing tank was novel for all fish in our study, and fish responding to automated stimulus exhibited significant reduction in both turn angle and the distance to bottom. These effects are in line with previous studies that show that social stimulus can alter individual fish’s behavioral response (Faustino et al, 2017; Mansur et al, 2014). Also, these effects further highlight the complexity of multifaceted anxiety behaviors in zebrafish that have been shown to be stimulus and context dependent (Luca & Gerlai, 2012; Seguin, Shams, & Gerlai, 2016).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The testing tank was novel for all fish in our study, and fish responding to automated stimulus exhibited significant reduction in both turn angle and the distance to bottom. These effects are in line with previous studies that show that social stimulus can alter individual fish’s behavioral response (Faustino et al, 2017; Mansur et al, 2014). Also, these effects further highlight the complexity of multifaceted anxiety behaviors in zebrafish that have been shown to be stimulus and context dependent (Luca & Gerlai, 2012; Seguin, Shams, & Gerlai, 2016).…”
Section: Discussionsupporting
confidence: 92%
“…For example, prior social experience determines preference for certain social (Moretz, Martins, & Robison, 2007) and environmental (Schroeder, Jones, Young, & Sneddon, 2014) stimuli, while social status in a group can affect stress level and immune responses (Filby, Paull, Bartlett, Van Look, & Tyler, 2010; Forsatkar, Safari, & Boiti, 2017). Presence of conspecifics can also alter individual behavioral responses to pharmacological treatments such as alcohol (Ladu, Butail, Macrí, & Porfiri, 2014) and pentylenetetrazole (Pagnussat et al, 2013) and to adverse stimuli such as alarm substance (Faustino et al, 2017) or the strongly illuminated area of the tank in a light/dark task (Mansur, Dos Santos, Dias, Pinheiro, & Gouveia, 2014). These studies highlight the need to control the social experience of zebrafish prior to and during the experiments and to consider the social environment for the analysis and interpretation of behavioral and physiological findings.…”
mentioning
confidence: 99%
“…Zebrafish exhibit social behavior since early stages of life 16 , preferring swimming in shoals 17 . In fact, behavioral and endocrine responses may differ according to the housing conditions and thus may be particularly influenced by group and/or isolation 18 19 20 , as well as environment complexity.…”
mentioning
confidence: 99%
“…Zebrafish are highly social animals that prefer swimming in groups ( Mansur Bde et al, 2014 ). The increase of IID and NND in the shoaling test indicated that zebrafish have decreased social cohesion ( Chen et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%